A structure calculation for hydrogen like nobelium - Güldem Ürer (Sakarya Üniversitesi Fen Bilimleri Enstitüsü Dergisi)
The hydrogenlike ion is the simplest structure of an atom, so the studying on it gives achange to test of methods using for determinating of atomic structures. It isalso an occasion the studying on hydrogen like ions to understand atomicstructure. For this reason, it is performed a study for hydrogen like nobelium(No101+, Z=102). The calculating level structure of No101+have been used both multiconfiguration Hartree-Fock and multiconfigurationDirac-Fock method. The calculations have contained some relativisticcorrections and quantum electrodynamic effects. There are very few theoreticalworks in available literature and no experimental one for No101+. Thecalculated results have been interpreted in comparison with other theoreticalresults.